Christian images and their jewish desecrators the history of an allegation, 400-1700 - Aron-Beller, Katherine (Philadelphia University of Pennsylvania Press, 2024)
In Christian Images and Their Jewish Desecrators, historian Katherine Aron-Beller analyzes the common Christian charge that Jews habitually and compulsively violated Christian images, identifying this allegation as one that functioned alongside other anti-Jewish allegations such as ritual murder, blood libel, and host desecration to ultimately inform dangerous and long-lasting prejudices in medieval and early modern Europe. Through an analysis of folk tales, myths, legal proceedings, and religious art, Aron-Beller finds that narratives alleging that Jews committed violence against images of Christ, Mary, and the disciples flourished in Europe between the fifth and seventeenth centuries. She then explores how these narratives manifested differently across the continent and the centuries, finding that their potency reflected not Jewish actions per se, but Christians' own concerns about slipping into idolatry when viewing depictions of religious figures. In addition, Aron-Beller considers Jews' own attitudes toward Christian imagery and the ways in which they responded to and rejected-or embraced-such allegations. By examining how desecration allegations affected Jewish individuals and communities spanning Byzantium, medieval England, France, Germany, and early modern Spain and Italy, Aron-Beller demonstrates that this charge was a powerful expression of the Christian majority's anxiety around committing idolatry and their eagerness to participate in practices of veneration that revolved around visual images-an anxiety that evolved through the centuries and persists to this day
In English
Keywords: Christian art and symbolism -- Mutilation, defacement, etc; Idolatry; Judaism -- Controversial literature -- History and criticism; History / Jewish; RELIGION / Christianity / Literature & the Arts; HISTORY / Medieval; RELIGION / Religious Intolerance, Persecution & Conflict; Aniconism; Antisemitic tropes; Byzantium; England; Europe; Iconoclasm; Jewish Desecration of Christian Art; Jewish attack of Christian images; Jews and Blood; antisemitism; blood libel; christ on the cross; christian jewish relations; conversion narrative; divine punishment; host desecration; legal judicial court case; medieval early modern history; mockery; morality tales; ritual murder; sacred image desecration; virgin mary